Hygienic Food Handling Practices and Associated Factors Among Food Handlers in Ethiopia: A Systematic Review and Meta-Analysis - Belay Negassa; Zemachu Ashuro; Negasa Eshete Soboksa (SAGE Publishing, 2022)
Background: The food handling practices of food handlers can have a significant impact on the hygienic status of the food. The aim of this study was to determine the prevalence and factors associated with hygienic food handling practices among food handlers in Ethiopia. Methods: PubMed, Science Direct, Google Scholar, and the Cochrane Library databases were used to find articles. Only cross-sectional studies that met the criteria for inclusion were considered. STATA version 16 statistical software was used to perform the meta-analysis. The study's heterogeneity was determined using Cochrane Q test statistics and the I 2 test. A random effect model was used to calculate the pooled prevalence of hygienic food handling practices. Results: To estimate the pooled prevalence of hygienic food handling practices in Ethiopia, 9 out of 33 reviewed studies were included. The prevalence of hygienic food handling practices was found to be 48.36% (95% CI: 39.74-56.99) in this study. Factors associated with hygienic food handling practices included; lack of food safety training (OR = 5.38; 95% CI: 1.71, 16.89), negative attitude (OR = 3.28; 95% CI: 1.50, 7.13), lack of access to handwashing facilities (OR = 4.84; 95% CI: 1.72, 13.65), lack of regular medical checkup (OR = 5.37; 95% CI: 3.13, 9.23), and lack of secondary education (OR = 2.51; 95% CI: 1.46, 4.32) among food handlers. Conclusion: In this study, the prevalence of hygienic food handling practices among Ethiopian food handlers was significantly low. Unhygienic food handling practices were attributed to a lack of food safety training, regular medical checkups, handwashing facilities, an unfavorable attitude toward food hygiene practices, and a lack of formal education. As a result, food handlers should receive ongoing food safety and hygiene training.